2020
DOI: 10.1186/s12967-020-02409-6
|View full text |Cite
|
Sign up to set email alerts
|

Duplications involving the long range HMX1 enhancer are associated with human isolated bilateral concha-type microtia

Abstract: Background: Microtia is a congenital anomaly of ear that ranges in severity from mild structural abnormalities to complete absence of the outer ears. Concha-type microtia is considered to be a mild form. The H6 family homeobox 1 transcription factor gene (HMX1) plays an important role in craniofacial structures development. Copy number variations (CNVs) of a downstream evolutionarily conserved enhancer region (ECR) of Hmx1 associated with ear and eye abnormalities have been reported in different animals, but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Duplications at 4p16.1 including HMX1 were also associated with OAVS 44 45. Of note, this duplication probably excludes the HMX1 downstream evolutionarily conserved enhancer region whose duplication is associated with bilateral concha-type microtia 46. Among other factors, HOXA2 is able to link this enhancer and interestingly, HOXA2 loss-of-function variants are also associated with bilateral microtia [MIM:612 290],47 48 whereas HMX1 biallelic loss-of-function variants are associated with oculoauricular syndrome [MIM:612 109] 49–51.…”
Section: Aetiologiesmentioning
confidence: 91%
See 1 more Smart Citation
“…Duplications at 4p16.1 including HMX1 were also associated with OAVS 44 45. Of note, this duplication probably excludes the HMX1 downstream evolutionarily conserved enhancer region whose duplication is associated with bilateral concha-type microtia 46. Among other factors, HOXA2 is able to link this enhancer and interestingly, HOXA2 loss-of-function variants are also associated with bilateral microtia [MIM:612 290],47 48 whereas HMX1 biallelic loss-of-function variants are associated with oculoauricular syndrome [MIM:612 109] 49–51.…”
Section: Aetiologiesmentioning
confidence: 91%
“…This specific non-coding genomic region was previously implicated in external ear development in vertebrates 87. Interestingly, HMX1 biallelic variants are associated with oculoauricular syndrome [MIM:612 109]51 whereas the specific duplication of HMX1 -ECR is linked to Concha-type microtia, an autosomal-dominant mild form of microtia 46. Several spontaneous animal models of microtia/ear dysplasia (cattle or sheep) are described as carrying duplications of the HMX1 -ECR88–90 (table 4).…”
Section: Oavs Animal Modelsmentioning
confidence: 99%
“…The 22q11.2 locus is regularly associated with OAVS, without clear pathophysiological mechanisms to explain it so far 23. 4p16 duplications involving HMX1 or his long-range enhancer were reported in OAVS individuals 24–26. Lastly, large 14q22.3 duplications were also associated with OAVS in three previous studies,27–29 and OAVS clinical features were described in a patient with an inversion breakpoint in 14q22.3 30.…”
Section: Introductionmentioning
confidence: 91%
“…Moreover, this study suggested a significant association and interaction between the duplication in the ECR near to HMX1 (OAR6) and the missense mutation in exon 7 of GATA6 (OAR23). Interestingly, a study (Si et al., 2020) reported that a duplication in the enhancer region of the HMX1 locus is associated with a type of microtia in humans. Furthermore, a study of this trait in Highland Cattle, utilising SNP‐chip genotyping and sequencing‐based fine mapping, also yielded HMX1 as a candidate locus (Koch et al., 2013).…”
Section: Introductionmentioning
confidence: 99%